Normalization of Cystic Fibrosis Immune System Reverses Intestinal Neutrophilic Inflammation and Significantly Improves the Survival of Cystic Fibrosis MiceSummary - Callie E. Scull; Yawen Hu; Scott Jennings; Guoshun Wang (Cellular and Molecular Gastroenterology and Hepatology)
Background & Aims: Cystic fibrosis (CF) is an autosomal recessive genetic disorder, affecting multiple organ systems. CF intestinal disease develops early, manifesting as intestinal bacterial overgrowth/dysbiosis, neutrophilic inflammation, and obstruction. As unresolvable infection and inflammation reflect host immune deficiency, we sought to determine if the CF-affected immune system plays any significant role in CF intestinal disease pathogenesis. Methods: CF and sibling wild-type (WT) mice underwent reciprocal bone marrow transplantation. After immune reconstitution, their mortality, intestinal transit, fecal inflammatory markers, and mucosal immune cell composition were assessed. Moreover, reciprocal neutrophil transfusion was conducted to determine if neutrophil function affects intestinal movement. Furthermore, expression of induced nitric oxide synthase (iNOS) and production of nitric oxide (NO) in CF and WT neutrophils were compared. Lastly, specific iNOS inhibitor 1400W was tested to prevent CF intestinal obstruction. Results: Immune restoration in CF mice reversed the intestinal neutrophilic inflammation, improved the intestinal dysmotility, and rescued the mice from mortality. Transfusion of WT neutrophils into CF mice ameliorated the retarded bowel movement. CF neutrophils expressed significantly more iNOS and produced significantly more NO. Pharmaceutical blocking of iNOS significantly improved intestinal transit and survival of CF mice. Conclusions: CF immune defect plays a critical role in CF intestinal disease development. Activation of iNOS in inflammatory cells produces excessive NO, slows the bowel movement, and facilitates intestinal paralysis and obstruction in CF. Thus, normalization of the CF immune system may offer a novel therapy to treat CF intestinal disease.